2017
DOI: 10.1080/09674845.2016.1271567
|View full text |Cite|
|
Sign up to set email alerts
|

British Journal of Biomedical Science in 2016. What have we learned?

Abstract: In 2016, the British Journal of Biomedical Science published 36 reports outlining specific advances in each of the various disciplines within biomedical science. These were one review, 25 original articles, 9 'In Brief' reports and one letter to the Editor. Of these, the majority were in blood science (5 in biochemistry, 7 in haematology and 2 in immunology) and infection science (8 in microbiology, 2 in virology) with a smaller number in cellular sciences (6 in cellular pathology and 2 in cytopathology). Thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 74 publications
(71 reference statements)
0
1
0
Order By: Relevance
“…Zhou et al [5] found in their research that, in patients with RA, miR-146a facilitated a pro-inflammatory phenotype of Tregs via increased STAT1 activation, and contributed thereby to RA pathogenesis. Abdulmaksoud et al [6] revealed that both miR-210 and miR-155 were closely related with RA disease activity. Serum miR-210 and miR-155 were two independent diagnostic markers for RA and could be served as non-invasive biomarkers for the diagnosis of RA.…”
Section: Introductionmentioning
confidence: 99%
“…Zhou et al [5] found in their research that, in patients with RA, miR-146a facilitated a pro-inflammatory phenotype of Tregs via increased STAT1 activation, and contributed thereby to RA pathogenesis. Abdulmaksoud et al [6] revealed that both miR-210 and miR-155 were closely related with RA disease activity. Serum miR-210 and miR-155 were two independent diagnostic markers for RA and could be served as non-invasive biomarkers for the diagnosis of RA.…”
Section: Introductionmentioning
confidence: 99%